Application of Amino Acids on Philippine Native Tomato (Lycopersicon esculentum L.) Grown Under Flood Condition - Catubis, Kent Marcial L.; Granada, Brenda A.; Morales, James B.; Alferez, Roger R.; Asentista, Raymund A.; Pascual, Pet Roey L.; Saramosing, Jovie G. (JPAIR Multidisciplinary Research, 2013)
Flooding is the most important abiotic stress in the tropical and subtropical regions that negatively affects terrestrial plant growth and productivity and even leading to plant death. Amino acid accumulation, on the other hand, may serve as defense during stress resulting to tolerance among others. Thus, a study was conducted to determine the growth, root length and number of leaves produced by Philippine native tomato as affected by different levels of amino acid under varying durations of flooding. Data were statistically analyzed through Analysis of Variance (ANOVA) for Randomized Complete Block Design (RCBD). Comparisons among means were done using Duncan's Multiple Range Test (DMRT). Shoot growth was increased with application of amino acids (100 ppm) after both flooding conditions (three and six days) at 3.28cm and 7.47cm, respectively. Moreover, no amino acid application or minimal amino acid application (100 ppm) produced the most number of leaves on unflooded and minimally flooded conditions (three days only). On root length, longer roots were produced by plants without amino acid (12.68 cm) or lesser amino acid (100 ppm) at 9.43 cm, while flooding had no significant effect on root length. These results clearly indicate the value of exogenous amino acid (100 ppm) application mainly on shoot growth of tomato. Furthermore, exogenous amino acid application is deemed necessary because even in both number of leaves and root length where results are comparable to without amino acid application, no negative effect was observed.
Keywords: agriculture; flooding; amino acid; Philippine native tomato